Ecogenomic insights into the resilience of keystone Blastococcus Species in extreme environments: a comprehensive analysis - Imed Sbissi; Farah Chouikhi; Faten Ghodhbane-Gtari; Maher Gtari (BMC Genomics)
Abstract Background The stone-dwelling genus Blastococcus plays a key role in ecosystems facing extreme conditions such as drought, salinity, alkalinity, and heavy metal contamination. Despite its ecological significance, little is known about the genomic factors underpinning its adaptability and resilience in such harsh environments. This study investigates the genomic basis of Blastococcus's adaptability within its specific microniches, offering insights into its potential for biotechnological applications. Results Comprehensive pangenome analysis revealed that Blastococcus possesses a highly dynamic genetic composition, characterized by a small core genome and a large accessory genome, indicating significant genomic plasticity. Ecogenomic assessments highlighted the genus's capabilities in substrate degradation, nutrient transport, and stress tolerance, particularly on stone surfaces and archaeological sites. The strains also exhibited plant growth-promoting traits, enhanced heavy metal resistance, and the ability to degrade environmental pollutants, positioning Blastococcus as a candidate for sustainable agriculture and bioremediation. Interestingly, no correlation was found between the ecological or plant growth-promoting traits (PGPR) of the strains and their isolation source, suggesting that these traits are not linked to their specific environments. Conclusions This research highlights the ecological and biotechnological potential of Blastococcus species in ecosystem health, soil fertility improvement, and stress mitigation strategies. It calls for further studies on the adaptation mechanisms of the genus, emphasizing the need to validate these findings through wet lab experiments. This study enhances our understanding of microbial ecology in extreme environments and supports the use of Blastococcus in environmental management, particularly in soil remediation and sustainable agricultural practices.